PRODUCTION AND CHARACTERIZATION OF ANTIBODIES TO TISSUE PLASMINOGEN ACTIVATOR: APPLICATION FOR THE PLATELET FLOW CYTOMETRY ASSAY - E. I. Yusova; T. V. Grinenko; T. O. Goncharenko; L. G. Kapustyanenko; A. A. Sobchenko; A. A. Tykhomyrov (Biotechnologia Acta, 2020)
Tissue plasminogen activator (tPA) is one of the key protein of plasminogen/plasmin system that converts plasminogen in the active proteinase plasmin. Platelets are able to bind both tPA and plasminogen on their surface, thus providing stimulatory effects on activation of zymogen. The present study was aimed to produce polyclonal antibodies against tPA and characterize their immunochemical capacities for further application in flow cytometry assay to study interaction between tPA and platelets. The experimental methods involved immunization of rabbit with tPA, collection of immune serum, synthesis of tPA-containing immunoaffine sorbent, ELISA, and flow cytometry. Polyclonal monospecific antibodies against tPA with high affinity to the antigen (Кd = 4.05・10–9 М) were obtained. Flow cytometry assay based on the use of the produced antibodies showed the presence of binding sites for tPA on the plasma membrane of inactive platelets. Moreover, agonist-stimulated platelets were revealed to expose more binding sites than their resting counterparts. Certain subpopulations of platelets that differ in the ability to bind tPA on their surface were also identified. Obtained data are of significant importance for further investigation of mechanisms underlying the role of platelets to regulate fibrinolytic rates.